RELIGIOUS MODERATION IN DIGITAL MEDIA-BASED LEARNING MODELS - Ima Maisaroh; Sujai Sujai; Burhanuddin Burhanuddin; Nina Yuliana (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to develop and examine the effectiveness of religious moderation in digital media based on the Dick and Carey learning model. The research is grounded in the increasing use of digital media as a primary source of religious information, which has the potential both to strengthen and to undermine the values of religious moderation. The study employed a qualitative approach with a Research and Development (R&D) design. The subjects were university students who actively use digital media. Data collection techniques included interviews, observations, questionnaires, and documentation, while data analysis followed the Miles and Huberman model. The results indicate that students’ understanding of religious moderation remains largely normative and is not yet accompanied by adequate digital literacy skills. The development of the Dick and Carey-based learning model produced interactive digital media, including educational videos, digital modules, and social media content. Implementation of the model demonstrated a significant improvement in students’ comprehension, tolerance, and critical thinking regarding religious content in digital media. Furthermore, the study found that integrating constructivist approaches, social learning, and digital literacy into the learning design effectively reinforced the internalization of religious moderation values. The developed learning model proved effective in enhancing student engagement and fostering inclusive and tolerant attitudes.In conclusion, promoting religious moderation in digital media requires a systematic, technology-based learning approach. This study provides both theoretical and practical contributions to the development of a learning model for religious moderation in the digital era.